Dermatomyositis as a manifestation of cancer - Przekazińska-Boager, Katarzyna; Brzezicka-Ciach, Urszula (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction . Dermatomyositis (DM) is an autoimmune disease that mainly affects skin and muscles. It has an incidence of approximately 5–10/1000 000 in adults. The association between dermatomyositis and internal organ cancers seems to be extremely important. Objective. The aim of this paper is to present a patient with dermatomyositis as a paraneoplastic syndrome. Case report . A 37-year-old woman was admitted to the Department of Dermatology due to skin lesions and proximal muscle weakness. The skin lesions consisted of edema and erythema of eyelids and neck; in addition erythema and papules were found above small joints of both hands. Based on the clinical presentation the diagnosis of dermatomyositis was established and systemic corticosteroid therapy (prednisone 60 mg/day) was introduced. Despite initial improvement, in the following days exacerbation of the disease was observed, and the patient reported severe vaginal bleeding. Gynecological consultation and histopathological examination were performed, which revealed cervical cancer. The patient was qualified for treatment with chemoradiotherapy. After completion of the treatment, the skin lesions and muscular symptoms resolved completely. Conclusions . According to different authors, the frequency of co-existence of dermatomyositis and internal organs cancers is estimated to be 6-45%. Most frequently DM is associated with ovary, lung and gastrointestinal cancer; and non-Hodgkin lymphoma. Cancer can be present before, during, or after the diagnosis of dermatomyositis, as it was in our patient. That is why it is so important to conduct the oncological search in this group of patients, especially in the absence of response to conventional therapy or with relapses of the disease.